The influence of model organosulfur extreme pressure additives and analogues on the corrosion of copper as measured by a wire corrosion test method. (4th January 2023) - Hunt, Gregory J.; Gahagan, Michael P.; Peplow, Mitchell A.
Abstract: A wire corrosion test (WCT) is used to investigate the influence of model organosulfur extreme pressure additives and analogues. The corrosion response from these compounds is discussed with regards to chemical structural type. Corrosion rates were calculated using the guide in ASTM G31 to provide a measurement in mm/year.